Recommendations for fetal echocardiography in twin pregnancy in 2016 - Leszczyńska, Katarzyna; Preis, Krzysztof; Respondek-Liberska, Maria; Słodki, Maciej; Wood, Dennis; Weiner, Stuart; Gembruch, Ulli; Rizzo, Giusseppe; Achiron, Reuven; Pruetz, Jay D; Sklansky, Mark; Cuneo, Bettina; et al. (Prenatal Cardiology, 2016)
Progress in the fields of fetal cardiology and fetal surgery have been seen not only in singleton pregnancies but also in multiple pregnancies. Proper interpretation of prenatal echocardiography is critical to clinical decision making, family counseling and perinatal management for obstetricians, maternal fetal medicine specialists, neonatologists and pediatric cardiologists. Fetal echocardiography is one of the most challenging and time-consuming prenatal examinations to perform, especially in multiple gestations. Performing just the basic fetal exam in twin gestations may take an hour or more. Thus, it is not practical to perform this exam in all cases of multiple gestations. Therefore our review and recommendations are related to fetal echocardiography in twin gestation.